Myotonic Dystrophy—A Progeroid Disease? - Meinke, Peter; Hintze, Stefan; Limmer, Sarah; Schoser, Benedikt (Frontiers in Neurology, 2018)
Myotonic dystrophies (DM) are slowly progressing multisystemic disorders caused by repeat expansions in the DMPK or CNBP genes. The multisystemic involvement in DM patients often reflects the appearance of accelerated aging. This is partly due to cataracts, muscle weakness, and frontal baldness, but there are also less obvious features like cardiac arrhythmia, diabetes or hypogammaglobulinemia. This results in the hypothesis that DM could be a segmental progeroid disease. To understand this characteristic appearance of accelerated aging we compare clinical features of DM to “typical” segmental progeroid disorders caused by DNA repair defects or mutations affecting the nuclear envelope. Furthermore, we investigate if this premature aging effect is also reflected on the cellular level in DM and looked into overlaps to “classical” progeroid disorders. Our comparison on a clinical and molecular level clearly qualifies DM as a segmental progeroid disorder. To further investigate the molecular similarities we used primary DM and control cell lines. They particularly showed overlaps to progeroid syndromes linked to the nuclear envelope.